Effect of certain drugs on blood biochemical profiles in cross breed cattle - SINGH, S P; SINGH, BALRAJ; SINHA, A K; SINHA, M P; MISHRA, S K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 60 1::ross bred cows which calved before three months but did not come into heat. Variousdrugs viz., Receptal (gr I), Urimin (gr 11), Minerex 6olus (gr III), Urimin plus Receptal (gr IV), Minerex bolus plus Receptal (grV) were used to induce estrus and one gr was kept as control (gr VI). Levels .of calcium, phosphorus, zinc and copper wereestimated in blood serum samples collected before treatment (0-day) and after treatment (on the day of first estrus) and thosewere found in increasing trend in all the groups on day of first estrus. Highest levels of zinc (286.70±14.980 mg/100 ml}°andcopper ( 184.69±6.690 mg/ I 00 ml) in blood serum on day offirst estrus were recorded in blood serum ofMinerex treated animals(gr III). Highest level of serum calcium ( I 0.25±0.298 mg/I 00 ml5 on day offirst estrus was noted in Minerex bolus plus Receptaltreated animals (gr V). Average serum phosphorus level on daioffirst estrus was highest (8.30±0.169 mg/ 100 ml) in Urimintreated animals (gr II). Differences in serum minerals levels between day of first estrus and 0-day in all the groups were highlysignificant (P < 0.01). Differences in Ca: P ratio between day of first estrus and 0-day were highly significant (P < 0.01) in all thegroups.
Keywords: Receptal; minerex bolus; urimin; calcium; phosphorus; zinc; copper; Ca:P ratio